Pengaruh Model Pembelajaran CERDAS terhadap Hasil Belajar Siswa pada Materi Nanoteknologi di Kelas X SMA Negeri 7 Prasetya Gorontalo - Zulfa K Muslimin; Mangara Sihaloho; Mardjan Paputungan; Julhim S. Tangio; Erni Mohamad; Thayban Thayban (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This research aimed to examine the effect of the CERDAS learning model on student learning outcomes. The research employed a quasi-experimental method with a non-equivalent prest-posttest control group design. The sample consisted of students from class X Merdeka 3, serving as the experimental group, and class X Merdeka 1 as the control group. Both from SMA Negeri 7 Prasetya Gorontalo. These classes were selected using purposive sampling. The research instrument was an objective test. The results revealed a significant difference in the average scores between the experimental and control classes. Specifically, the average student learning outcome in the experimental group was 79,77, while in the control group, it was 67,27. Hypothesis testing using the t-tes yielded tcount value > ttable, indicated the tcount (2,99) was greater than the ttable value (2,01), which led to the rejection of H0 and confirmation of H1, Confirming that the CERDAS learning model had a significant effect on student learning outcomes. Additionally, the N-Gain test showed a moderate effect (0,68), indicating that the CERDAS learning model is fairly effective in improving student learning outcomes.